Assessment of Human Capital Attributes Influencing Occupational Diversification among Rural Women in Anambra State, Nigeria - E.N, Ajani; E.M, Igbokwe (International Journal of Sustainable Agricultural Research, 2015)
The study was carried out in Anambra State, Nigeria to assess the influence of human capital attributes on occupational diversification among rural women. Simple random sampling technique was used in selecting 462 respondents for the study. Data was collected using questionnaire. Descriptive statistics such as percentage mean scores, standard deviation; factor analysis and correlation were used for data analysis. Results show that the respondents were mostly influenced by certain human capital attributes namely; possession of entrepreneurial skills (59.5%), number of dependants in the household (55.4%), access to information on changing demand patterns (52.6%) 52.4% and perceived health status (52.4%). They were also highly constrained by lack of women empowerment training programmes in rural areas (M= 3.5), poor skill training (M= 3.5), inadequate training opportunities (M= 3.4), poor educational attainment (M= 3.3), among others. Developing skills in rural women are keys to improving rural productivity, employability and income-earning opportunities, enhancing food security and promoting environmentally sustainable rural development and livelihoods. It was recommended that adult literacy programmes should be introduced by government and non-governmental organizations in order to help the rural women to acquire necessary education that will help them in occupational diversification. It highlights the development of human capital among rural women in order to equip them with the necessary skills to work in various occupations gainfully employed for higher returns.